A review on thermochemical seasonal solar energy storage materials and modeling methods - Abdullah; M. Koushaeian; N. A. Shah; J. D. Chung (International Journal of Air-Conditioning and Refrigeration, 2024)
Abstract In the current era, national and international energy strategies are increasingly focused on promoting the adoption of clean and sustainable energy sources. In this perspective, thermal energy storage (TES) is essential in developing sustainable energy systems. Researchers examined thermochemical heat storage because of its benefits over sensible and latent heat storage systems, such as higher energy density and decreased heat loss. Solar energy is a promising alternative among the numerous renewable energy sources. As a result, this study provides an overview of thermochemical heat storage materials, focusing on materials utilized by solar energy systems in buildings. The research examines the storage materials used in relevant studies and the models used to predict and enhance system performance.